Level of aspiration of the youths in Barangay Sinubsuban, Maasin and their attitudes towards community development programs. - Lulu, Reynaldo C.
The study of youths in Barangay Sinubsuban, Maasin was made to find out their levels of aspirations and how these affect their attitudes towards the development programs (activities); To know the levels of aspirations of the in-school and out-of-school youths; To find out their attitudes towards the barangay development programs. The researcher believes that the findings of this study will be of importance to further the government's goal for community development in general., The data were gathered by the use of the interview guide to fifty youths categorized into two, those whose ages are from 15-26 who stopped schooling or known as the Out-of-school (OSY) and those who belong to the same range of age who were studying or the In-School-Yputh (ISY). Simple random sampling method was used in the selection of the respondents. In situations were the interview guide was deemed inadequate, two other methods were used in the collection of data-the survey and the case study. The data were taken through a face-to-face personal interview which includes the background information of the respondents, their aspirations, and their attitudes towards community development programs. The whole research activity was divided into three stages, namely: (1) the initial phase which was devoted almost entirely to planning and reaching out of important clues that could enable the researcher to start systematically with his work; (2) a primary phase which covered the period for data collection interviewing the respondents; (3)and a final phase which comprises the last two days of the researcher in the area of the study and the period when he was corresponding with native informants. Descriptive analysis were used to describe the data gathered using frequency counting, percentages, and averages. Rank correlation was used to measure all items which required ranking. The participation and attitudes of the respondents towards the programs were measured by using the four-point scale. Three-point-scale was used to rate the usefulness of the programs. A Chi-square test was used to determine the relationships between the independent and the dependent variables. The findings revealed that the youths have low levels of aspirations. This was shown by their low yearning desires for themselves and for their community in general. Furthermore, the result revealed that the educational attainment of the youths is related with their level of aspiration. However, majority of the youths have only attained elementary education. The level of aspiration of the youths is independent on their parents' occupation. On family size, the findings revealed that the level of aspiration of the youths is dependent on the family size. Family income is not related to the level of aspiration of the youths. The hypothesis that the ISY have more favorable attitudes towards the development programs than the OSY is significant. Regarding their participation and involvement, the ISY have higher weighted scores than the OSY in all programs. Also, with regards to their attitudes towards the programs or activities, the ISY have higher weighted scores than the OSY. However, the latter have higher aspirations for the improvements of their barangay than the former. Therefore to answer the question whether the levels of aspirations of the youths affect their attitudes towards community development programs, the findings revealed that only few were active participants in the activities of the programs as suggested by their low aspirations. Despite their low aspirations the youths should not be taken for granted . Some of their ideas were worth considering, thus, they should be motivated to take active participation in the community activities. They have hidden talents and potentials. Recognition of these factors would be considered in order for the youths to take active participation in community development.